Neutrophil CD64–a prognostic marker of sepsis in intensive care unit: a prospective cohort study - Pham, Huy Minh; Nguyen, Duy Ly Minh; Duong, Minh Cuong; Phan, Xuan Thi; Tran, Linh Thanh; Trang, Duong Hong Thuy; Pham, Thao Thi Ngoc (Frontiers in Medicine, 2023)
Little is known about the prognostic ability of nCD64 in critically ill patients. This study aimed to assess the prognostic values of nCD64 in adult ICU patients with sepsis.A prospective cohort study was conducted at the ICU of Cho Ray Hospital in Vietnam between January 2019 to September 2020. All newly admitted 86 sepsistic patients diagnosed based on sepsis-3 criteria were included. An evaluation of nCD64 was performed at admission (T0) and 48 hours thereafter (T48). Delta nCD64 (nCD64 T48 -nCD64 T0), %delta nCD64 ((nCD64 T48 -nCD64 T0)/nCD64 T0 x 100%), APACHE II and SOFA scores were calculated and examined. Serum procalcitonin levels and white blood cell counts were documented.Spearman's rank correlation coefficient was used to test the correlation between nCD64 and severity scores. Receiver-operating characteristic (ROC) curve was performed to evaluate the predictive efficacy of the sepsis parameters.Patients with septic shock had significantly higher nCD64 levels than sepsistic patients (3,568 [2,589;5,999] vs. 1,514 [1,416;2,542] molecules/cell, P<0.001). nCD64 T0 and SOFA scores had a moderately positive linear correlation (R = 0.31, P = 0.004). In the survivor group, nCD64 levels significantly decreased within the first 48 hours of admission (P<0.001), while this trend was not statistically significant in the non-survivor group (P=0.866). The area under the ROC curve (AUC) value of %delta nCD64 combined with APACHE II score (0.81) was higher than that of any other parameter alone or in combination with each other.The nCD64 index may serve as a valuable biomarker for predicting the course of sepsis.Monitoring changes in nCD64 during the initial 48 hours of admission can aid in predicting the prognosis of septic patients. The use of a combination of the trends of nCD64 index in the first 48 hours with APACHE II score would further enhance the predictive accuracy. More studies with longer follow-ups are needed to fully understand the implications of serial trend and kinetics of nCD64 in sepsistic patients.